Can periprosthetic hip joint infections be successfully managed by debridement and prosthesis retention? - Anagnostakos, Konstantinos (Baishideng Publishing Group Inc, 2014)
To evaluate the current literature about how successfully periprosthetic hip joint infections can be managed by debridement and prosthesis retention. A literature search was performed through PubMed until September 2013. Search terms were “DAIR (debridement, antibiotics, irrigation, and retention)” alone and in combination with “hip” as well as “hip infection + prosthesis retention”. A total of 11 studies reporting on 292 cases could be identified. Five different treatment modalities have been described with varying success rates (debridement-21% infection eradication rate; debridement + lavage-75% infection eradication rate; debridement, lavage, with change of modular prosthesis components-70.4% infection eradication rate; debridement, lavage, change of modular prosthesis components + vacuum-assisted closure-92.8% infection eradication rate; acetabular cup removal + spacer head onto retained stem-89.6% infection eradication rate). With regard to the postoperative antibiotic therapy, no general consensus could be drawn from the available data. Debridement, antibiotic therapy, irrigation, and prosthesis retention is an acceptable solution in the management of early and acute hematogenous periprosthetic hip joint infections. The current literature does not allow for generalization of conclusions with regard to the best treatment modality. A large, multi-center study is required for identification of the optimal treatment of these infections.